Perspectivas de uso de formulação de Azospirillum brasiliense via foliar em linhagens de sorgo - Erika Manuela Goncalves Lopes (2019)
The objective of this work was to characterize the main agronomic and nutritional quality attributes of the grains of different sorghum strains submitted to nitrogen fertilization with urea and Azospirillum brasilense in the semiarid region. The experimental design was 8 x 2 factorial blocks, constituting sorghum strains with two types of nitrogen fertilization (urea and. Biological fertilization was also efficient to fertilize with urea for the height of plants, detergent-acid fiber (FDA) and detergent neutral fiber (NDF) to all sorghum seeds studied. LB26, LR276 and LR277 were the most prominent strains in productive terms and grain quality, when they were followed as other rows. The LR277 line presented growth rates of cover types, urea and A. brasilense, while LB26 and LR276 increased the potential of use of chemical fertilization with the increase in the productive indexes when used in cover fertilization. As lineages, LR276 and LR277, higher load content when fertilized in cover with A. brasilense.